(3eSGgeI aj TQM hJhVjM GdfXQjGJ GdGbJUGOjIs - (3YGeQ(B, (3dWajs; (3GSeGYjd(B, (3eQhIs ((3OeTb(B:s (3OGQ GdQVG ddfTQ(B,s, 2002)
(3GdGbJUGO ef hLgI fXQ GddhQO ejfQO cjfR hCJHGYg,GdGbJUGO ef hLgI fXQ BOe SejK hhQKJg,GdGbJUGO HMSH cGQd eGQcS hJdGePJg,GdGbJUGO HMSH LhRja BdhS TheHjJQ hGdJjGQGJ GdeJaQYI Yfg(B((3GdgQWbI Ydi GdWQjbI GdTheHjJQjIs
(3HHdjhZQGajG(B:(3U(B.289-291s
Keywords: (3GdGbJUGO(B-(3fXQjGJs